Calibration and validation of three evapotranspiration models in a tea field in the humid region of south‐east China. (25th May 2022) - Zhang, Chuan; Li, Lanlan; Yan, Haofang; Ou, Mingxiong; Akhlaq, Muhammad; Zhang, Wencheng; Huang, Song
Abstract: Evapotranspiration (ETc ) is the most important part of agricultural water consumption. Accurate determination of the ETc of tea trees is important in the water management of tea fields. In this study, three models, the Penman–Monteith (PM), Priestley–Taylor (PT) and crop coefficient (KC) models, were applied and calibrated using meteorological data of 2017 in a tea field. The calibrated models were validated using the Bowen ratio energy balance (BREB) method with the data of 2018 and 2019 in the tea field. The canopy resistance of the PM model was calibrated by the inverse method with the BREB‐measured ETc using the Katerji and Perrier (KP) submodel with R 2 equal to 0.80. The annual mean value of the coefficient in the PT model ( α =  1.03) was determined based on the BREB results and meteorological data. In addition, the crop coefficients of tea trees based on the measured ETc and reference evapotranspiration (ET0 ) were comprehensively evaluated, with values of 0.86, 1.19 and 0.96 at the three growth stages, showing a cyclical evolution within a year. The PT model performed best, with a root mean square error (RMSE) equal to 0.82 mm day −1 and a Nash–Sutcliffe efficiency (NSE) equal to 0.90. The PM model underestimated ETc with RMSE equal to 0.79 mm day −1 and NSE equal to 0.84, while the KC method overestimated ETc . Résumé: L'évapotranspiration est la part la plus importante de la consommation d'eau en agriculture. La détermination précise du ETc des théiers est importante dans la gestion de l'eau des champs de thé. Dans cette étude, trois modèles, les modèles Penman–Monteith (PM), Priestley–Taylor (PT) et crop coefficient (KC), ont été appliqués et calibrés à l'aide de données météorologiques à partir de 2017 dans un champ de thé. Les modèles calibrés ont été validés en utilisant la méthode BREB (Bowen ratio energy balance) avec les données de 2018 et 2019 dans le champ de thé. La résistance du couvert du modèle PM a été calibrée par la méthode inverse avec le modèle BREB mesuré ETc, en utilisant le sous‐modèle Katerji et Perrier (KP) avec R2 égal à 0.80. La valeur moyenne annuelle du coefficient dans le modèle PT ( p  = 1, 03) a été déterminée sur la base des résultats du BREB et des données météorologiques. En outre, les coefficients de culture des théiers basés sur l'évapotranspiration mesurée et l'évapotranspiration de référence (ET0) ont fait l'objet d'une évaluation complète, avec des valeurs de 0.86, 1.19 et 0.96 aux trois stades de croissance, montrant une évolution cyclique au cours d'une année. Le modèle PT a donné de meilleurs résultats, avec une erreur quadratique moyenne (RMSE) égale à 0, 82 mm d‐1 et une efficacité de Nash–Sutcliffe (NSE) égale à 0, 90. Le modèle PM a sous‐estimé ETc avec RMSE égal à 0, 79 mm d‐1 et NSE égal à 0.84, tandis que la méthode KC a surestimé ETc.